An Amalgamation of Women’s Reality and Male Fantasy: Constructing Gender in Neil Gaiman’s The Ocean at the End of the Lane - Lindgren, Emma (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis discusses the construction of gender through the gaze of a male narrator in Neil Gaiman’s novel The Ocean at the End of the Lane. As the narrator, the nameless protagonist only sees partial views of the woman characters around him. These partial views do not represent the entirety of the women’s beings; instead, they only reflect what he sees and thinks of the women. As a result, the narration is influenced by the protagonist’s worldviews and the women are described as stereotypical caricatures. The purpose of this thesis is to continue the ongoing feminist discussion on gender stereotypes, the misrepresentation of women, and the way these affect consumers and consequently the society. I will examine how two specific gender stereotypes, the so-called Triple Goddess archetype and the virgin-whore dichotomy, are used to label the woman characters as either good or bad. This is in order to show the effect of gender stereotypes in the real world.